2009
DOI: 10.1073/pnas.0901726106
|View full text |Cite
|
Sign up to set email alerts
|

Interference of mismatch and base excision repair during the processing of adjacent U/G mispairs may play a key role in somatic hypermutation

Abstract: In eukaryotic mismatch repair (MMR), degradation of the errorcontaining strand initiates at nicks or gaps that can be up to a kilobase away from the mispair. These discontinuities may be the ends of Okazaki fragments or the 3 -termini of the leading strands during replication, whereas the termini of invading strands may fulfill this role during recombination. Here we show that, in extracts of human cells, MMR can initiate also at sites of ongoing base excision repair. Although unlikely under normal circumstanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 27 publications
9
88
0
Order By: Relevance
“…Specifically, that MutSα/MutLα activated by binding to a U/G mismatch might "hijack" a cleaved abasic site generated by the sequential action of uracil DNA glycosylase (UDG) and AP-endonuclease APE1 during the processing of a nearby U/G mismatch that was being processed by BER (Figure 3Ac). This was indeed the case in vitro: when BER was inhibited, so was MMR [20]. This study clearly demonstrated that BER intermediates can be utilized as EXO1 entry points during MMR.…”
Section: Mmr Proteins In Antibody Maturationsupporting
confidence: 58%
See 2 more Smart Citations
“…Specifically, that MutSα/MutLα activated by binding to a U/G mismatch might "hijack" a cleaved abasic site generated by the sequential action of uracil DNA glycosylase (UDG) and AP-endonuclease APE1 during the processing of a nearby U/G mismatch that was being processed by BER (Figure 3Ac). This was indeed the case in vitro: when BER was inhibited, so was MMR [20]. This study clearly demonstrated that BER intermediates can be utilized as EXO1 entry points during MMR.…”
Section: Mmr Proteins In Antibody Maturationsupporting
confidence: 58%
“…We could show that strand breaks or gaps generated during base excision repair (BER) could be utilized for MMR initiation [20]. Most recently, S. cerevisiae polymerase-ε, which catalyzes the synthesis of the leading strand [21], was shown to occasionally incorporate also ribonucleotides into DNA during replication [22].…”
Section: Repair Of Base/base Mismatches and Idlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism of SHM and its target selection is incompletely understood, activation-induced cytidine deaminase (AID) (4,5), which converts cytosine into uracil, for example, in the RGYW motif, initiates SHM by converting a C:G base pair to a U:G mismatch. Removal of the U by uracil-DNA glycosylase (UNG) generates an abasic site in the DNA, which may lead to a variety of base substitutions (6)(7)(8). For the WA motif, it is suggested that after AID-dependent deamination of a cytosine, recognition of the U:G mismatch by mismatch repair protein MutSα (MSH2-MSH6 heterodimer, in which MSH stands for MutS Homolog) leads to the recruitment of DNA polymerase η (Pol η), and with an incision made by UNG the ensuing short-patch repair synthesis results in mutations of A:T pairs to G:C (Fig.…”
Section: π-Cation Stacking | A-to-g Transition | Immunoglobulinmentioning
confidence: 99%
“…10) is subsequently filled in by DNA Pols, including error-prone translesion Pols, which spreads mutations beyond the initiating AID-induced lesion. The combined, but noncompeting interaction of the UNG and MMR pathways in generating mutations at A:T base pairs (bp) has been described (10)(11)(12). This mismatch repair-dependent process has been termed phase II of SHM (3).…”
mentioning
confidence: 99%